Integrated use of organic and inorganic sources of nutrients in french bean (Phaseolus vulgaris) - RAJIV; TOMAR, SAURABH (The Indian Journal of Agricultural Sciences, 2022)
The present experiment was conducted during winter (rabi) season of 2017–18 and 2018–19 to study the effect of integrated use of organic and inorganic sources of nutrients on french bean (Phaseolus vulgaris L.). The experiment was laid out in randomized block design with seven treatments of inorganic fertilizers (NPK 80:80:40 kg/ha) along with organic source combinations (25, 50 and 75% N through FYM and vermicompost) tested against the control (no fertilizer). Based on 2 years’ pooled data, application of 75% NPK through inorganic source + 25% N through vermicompost produced highest number of pods/plant (25.98), pod length (14.38 cm), pod width (1.29 cm), average single pod weight (4.33 g), green pod weight/plant (41.67 g) and green pod yield (7.71 t/ha) and earned maximum net return of `1,12,212.0/ha. The treatment with 100% NPK through inorganic source @80:80:40 kg/ha produced green pod yield of 6.17 t/ha with net return `83,225.0/ha. The B:C ratio (3.67) was also higher under the treatment with 75% NPK through inorganic source + 25% N through vermicompost. Inorganic fertilizers (75% NPK) and vermicompost (25% N) proved to be the best treatment for enhancing yield and economics of french bean under central plain zone of Uttar Pradesh. Therefore, the practice of 75% NPK through inorganic integration with 25% N through vermicompost may serve as alternative of NPK inorganic fertilizers and may also be recommended to exploit the better eco-friendly economic green pod yield of french bean.